Hak Cipta dalam Sorotan: Gugatan VISI dan Tantangan Hukum di Industri Musik - Margaret, Felicia; Laksana, Angelia; Pradigdo, Yolanda Yuliani; Sugianto, Fajar (Anthology: Inside Intellectual Property Rights, 2025)
The Indonesian music industry has experienced rapid growth which has brought significant challenges in copyright protection, particularly regarding digital piracy and the inequities in the distribution of royalties. Although Law No. 28 of 2014 on Copyright provides protection for songwriters, performers, and record producers, its implementation in practice faces numerous obstacles. Digital piracy and illegal distribution of music works threaten the economic rights of musicians, while the unequal distribution of royalties often harms the creators. Many musicians do not receive fair compensation for their creations, while industry players reap much greater profits. This issue has led VISI to file a judicial review request of the Copyright Law, which it views as insufficient in protecting the rights of creators. This study aims to analyze the normative weaknesses in the Copyright Law, evaluate its implementation on the ground, and identify the injustices experienced by creative professionals. The approach used is a normative juridical one, focusing on legal evaluation and the realities on the ground regarding copyright violations and the distribution of royalties. This study also examines the role of collective management organizations in the oversight and distribution of royalties. The results are expected to provide recommendations for improving the legal system to be fairer and more effective in protecting the copyright of music works. Thus, it is hoped that better protection for music creators can be achieved, thereby supporting the sustainability of the Indonesian music industry while also creating a balance in the distribution of profits between musicians and the industry. Bahasa Indonesia Abstrak: Industri musik Indonesia mengalami perkembangan pesat di era digital yang membawa tantangan besar dalam perlindungan hak cipta, terutama terkait pembajakan digital dan ketidakadilan dalam pembagian royalti atas lagu dan musik. Meskipun Undang-undang Nomor 28 Tahun 2014 tentang Hak Cipta telah mengatur perlindungan bagi pencipta lagu, pelaksana, dan produser rekaman, penerapannya dalam praktik masih mengalami banyak hambatan. Pembajakan digital dan distribusi ilegal karya musik mengancam hak ekonomi para musisi, sementara ketimpangan dalam pembagian royalti sering kali merugikan pencipta karya. Banyak musisi tidak mendapatkan imbalan yang layak atas karyanya, sedangkan pihak industri memperoleh keuntungan yang jauh lebih besar. Hal ini yang kemudian melatarbelakangi asosiasi VISI untuk mengajukan permohonan uji materi atas UU Hak Cipta yang dirasa kurang dapat melindungi hak dari para pencipta karya. Penelitian ini bertujuan untuk menganalisis kelemahan normatif dalam UU Hak Cipta terkait industri musik, mengevaluasi implementasinya di lapangan, serta mengidentifikasi ketidakadilan yang dialami pelaku kreatif. Pendekatan yang digunakan adalah yuridis normatif dengan fokus pada evaluasi hukum dan realitas di lapangan terkait pelanggaran hak cipta serta distribusi royalti. Penelitian ini juga mengkaji peran lembaga manajemen kolektif dalam pengawasan dan distribusi royalti. Hasil penelitian diharapkan memberikan rekomendasi perbaikan sistem hukum yang lebih adil dan efektif dalam melindungi hak cipta karya musik. Dengan demikian, diharapkan dapat tercipta perlindungan yang lebih baik dan memadai bagi para kreator musik sehingga dapat mendukung keberlanjutan industri musik Indonesia sekaligus menciptakan keseimbangan dalam pembagian keuntungan antara musisi dan industri.